2016
DOI: 10.1155/2016/1323614
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of AllocationCSRPlant Functional Types in Northern Europe

Abstract: Morphological and physiological parameters of 76 vascular plant species typical for Northern Europe were analyzed using Grime's classification. species (competitors) have high levels of canopy height, leaf dry weight, and maximal lateral spread. species (ruderal) have low leaf dry weight, longer flowering period, high rate of photosynthetic capacity and respiration, and high nitrogen content in the leaves. Stress-tolerant ( ) species prevailing in habitats with limited resources are small and have low rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Third, it is possible that long and late-flowering species were indirectly selected in urban areas by hitch-hiking (Smith & Haigh, 1974) along with other plant characteristics under direct selection. Indeed, our results revealed that the flowering period was also related to the ecological strategies of the plants and to the degree of autogamy, which is consistent with a significantly longer and later flowering period of R-strategists compared with S-and C-strategists recently shown by Novakovskiy, Maslova, Dalke, and Dubrovskiy (2016). Munoz, Violle, and Cheptou (2016) observed recently from a 2,000-species dataset that ruderal species were mostly autogamous, while competitive species were more often allogamous, and stress-tolerant species tended to have a mixed mating system.…”
Section: Ecological Strategies and Flowering Phenologysupporting
confidence: 89%
See 1 more Smart Citation
“…Third, it is possible that long and late-flowering species were indirectly selected in urban areas by hitch-hiking (Smith & Haigh, 1974) along with other plant characteristics under direct selection. Indeed, our results revealed that the flowering period was also related to the ecological strategies of the plants and to the degree of autogamy, which is consistent with a significantly longer and later flowering period of R-strategists compared with S-and C-strategists recently shown by Novakovskiy, Maslova, Dalke, and Dubrovskiy (2016). Munoz, Violle, and Cheptou (2016) observed recently from a 2,000-species dataset that ruderal species were mostly autogamous, while competitive species were more often allogamous, and stress-tolerant species tended to have a mixed mating system.…”
Section: Ecological Strategies and Flowering Phenologysupporting
confidence: 89%
“…Indeed, our results revealed that the flowering period was also related to the ecological strategies of the plants and to the degree of autogamy, which is consistent with a significantly longer and later flowering period of R-strategists compared with S-and C-strategists recently shown byNovakovskiy, Maslova, Dalke, and Dubrovskiy (2016). Indeed, our results revealed that the flowering period was also related to the ecological strategies of the plants and to the degree of autogamy, which is consistent with a significantly longer and later flowering period of R-strategists compared with S-and C-strategists recently shown byNovakovskiy, Maslova, Dalke, and Dubrovskiy (2016).…”
supporting
confidence: 90%
“…At site 3AC, the tree stand (total canopy density 0.6) was dominated by deciduous trees. The decrease of the illumination level under the canopy of the young stand (Degteva, ), reduction of N caused by active tree regrowth, and increasing C‐species competition (Novakovskiy et al, ) resulted in a decrease in species richness compared to site 2AC. Ruderal species dropped out from the community, and plants typical of natural communities (forests and meadows) strengthen their positions (e.g., Geranium sylvaticum ).…”
Section: Discussionmentioning
confidence: 99%
“…A dominant classification approach was used. The grime plant functional types system was used to assess the functional types of plants (Novakovskiy, Maslova, Dalke, & Dubrovskiy, 2016). Nomenclature for vascular plants is given according to Czerepanov (1995), for mosses - Ignatov and Afonina (1992) and for lichens -Santesson, Moberg, Nordin, Tønsberg, and Vitikainen (2004).…”
Section: Vegetation Study Soil Sampling and Analysismentioning
confidence: 99%
See 1 more Smart Citation